Adequate formal language performance in unilateral cochlear implanted children: Is it indicative of complete recovery in all linguistic domains? Insights from referential communication. Issue 4 (April 2015) - Mancini, Patrizia; Dincer D'Alessandro, Hilal; Guerzoni, Letizia; Cuda, Domenico; Ruoppolo, Giovanni; Musacchio, Angela; Di Mario, Alessia; De Seta, Elio; Bosco, Ersilia; Nicastri, Maria
Abstract Objectives Referential communication (RC) is a key element in achieving a successful communication. This case series aimed to evaluate RC in children with unilateral cochlear implants (CIs) with formal language skills within the normal range. Methods and materials A total of 31 children with CIs, with language development within the normal range, were assessed using the Pragmatic Language Skills test (MEDEA). Results Of the children with CIs, 83.9% reached performance levels appropriate for their chronological ages. The results confirmed a positive effect of cochlear implantation on RC development, although difficulties remained in some CI users. Conclusions The outcomes emphasize the need to pay greater attention to the pragmatic aspects of language, assessing them with adequate testing in the early phase after cochlear implantation. Clear knowledge of children's communicative competence is the key in optimizing their communicative environments in order to create the basis for future successful interpersonal exchanges and social integration.